A study on the effect of slotted airfoil on the performance of Darrieus vertical axis wind turbines in different wind regions - Liqi Luo; Qiuyun Mo; Yuefeng Li; Tao Jiang; Yinglei Zhao (PLoS ONE, 2025)
Slotted airfoils mitigate the flow separation on the blades operating at high angles of attack in the upwind region, consequently augmenting the power coefficient and reducing the startup wind speed of Darrieus vertical axis wind turbines (VAWTs). Nonetheless, the presence of the slot structure alters the original flow dynamics, inducing flow separation when the blade operates in the downwind region and at elevated blade tip speed ratios (TSR), which leads to a reduction in the blade’s power coefficient. This study establishes an aerodynamic model of the flow field migration around the blade surface by utilizing the lattice Boltzmann method in conjunction with large eddy simulation to ascertain the influence of the inlet and outlet positions of the slot on the flow field structure across different wind regions. The simulations indicate that, under the downwind region and at high TSR, positioning the slot at the midsection of the blade, although it expands flow separation near the trailing-edge, does not disrupt the primary flow at the leading-edge. Unexpectedly, the slot optimizes the pressure distribution on the pressure side of the blade, thereby enhancing the blade’s performance in the downwind region. At a TSR of 3.3, the average power coefficient of the blades in the downwind region increases by up to 63.62%. These results offer valuable insights for the implementation of slotted airfoils to enhance energy conversion efficiency in VAWTs’ design optimization.